(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
In the present work, density functional theory and time-dependent density functional theory were employed to investigate the hydrogen-bonded charge transfer complex of 5-aminoquinoline (5AQ) and picric acid (PA) at B3LYP/6-31G(d,p) level in the gas phase as well as CHCl\(_3\). The geometrical parameters, optimization energies, interaction energies, frontier molecular orbitals (FMOs), and ground-state dipole moment were considered, which supported the stability of the complex. Hence, the theoretical study of the 5AQ-PA complex provides valuable information about its molecular structure, possible interaction sites and electronically excited states.